The impact of sowing structure on proftability of family farms directed at the fnal production of fattened beef cattle - Todorović, Saša; Filipović, Nikola; Paunović, Tamara (Economics of Agriculture, 2010)
Small and inadequately used estates of family farms limit the capacities of cattle production because of limited forage production which is the basis of farm economic sustainability. Insuffcient and inadequate use of soil resources leads to the decrease of their competitiveness which also results in the need of fnding more rational ways of their organization. Bearing that in mind, the decision on buying mercantile maize on the market instead of producing it on the farm is taken into consideration. As a consequence of the previous decision, the possibility of the change of sowing structure is raised. Applying partial budget analysis, it was examined whether the decision on buying mercantile maize on the market and changing the sowing structure was economically justifed and under what conditions using additional procedure of sensitive analysis. Applying this approach, it was investigated to what extent that decision contributed to improving the proftability of family farm. The results of the conducted research show that buying mercantile maize on the market will enable changes in the sowing structure, that is, buying mercantile maize will make the area free, which according to some conservative estimations, can be used for production of suffcient amounts of alfalfa hay and silage maize for fattening of additional 19 head. In addition, it is shown that more rational way of organising family farms directed at the fnal production of fattened beef cattle can additionally use available resources and in that way increase proftability and improve competitiveness.